Descolonizar e afrocentrar a educação infantil : corpo negro e cabelo crespo nas experiências e narrativas de crianças e professoras - SILVA, Keise Barbosa da (2022)
This research came to light from concerns about the discussion on racism and racial issues related to childhood in which the general objective is to investigate alongside protagonists of educational process in Early Childhood Education (children and teachers) how Education for Ethnic-Racial Relations contributes to the appreciation of black body and curly hair, regarding Decolonial and Afrocentric pedagogical perspectives. The specific objectives include (1) To analyze socialization situations in the school context in which children express notions and designations about the black body and curly hair; (2) To identify which attributions the children give to the representations of the black body and the curly hair; (3) To understand how the initial formation of early childhood education teachers contributes to the implementation of Law nº 10.639/03 in their pedagogical practices and (4) To identify teachers' experiences and narratives about black bodies and curly hair, based on the Pedagogical formation meetings/workshops in a Decolonial and Afrocentric perspective. Studying about black body and curly hair as important elements of black identity that are present in educational processes, whether in or outside school, can point out ways that go beyond the denunciation of racism and the reproduction of stereotypes and prejudices. Also, it may present a resignification of the African cultural elements, which brings us into contact with African history, memory and ancestry. This research, therefore, proposes to think about the black body and curly hair as important instruments of political awareness and racial empowerment in a process against racial and colonial oppression. Contributions of studies on childhood are also presented, understanding that this period of life does not occur in the same way for all children and that the experience of this biographical moment is crossed by several social markers, including the racial one. Problematize how education should rethink its hegemonic and decontextualized practices, including the discussion of racial difference in curricula and pedagogical practices and that can, beyond the curriculum, re-signify the marks of coloniality present in discourses and school practices from the contributions of Decolonial Pedagogy and Afrocentric Education. In this sense, the present work is outlined as a qualitative research that followed two methodological paths: the case study with the children of Group 4 at the CMEI from the Municipal Department of Education in Recife and the intervention research with early childhood teachers from the online focus group. Considerations and results of this research reveal a school that has (re)produced racist and discriminatory practices by daily reaffirming the subordinate place of black people in society with discourses that range from school content to care practices aimed at bodies that meet the Eurocentric norm. What this investigation seeks to highlight is the urgency of public policies in early childhood education focused on Ethnic-racial diversity and that recognize and dialogue with the historical struggles of black population, as well as investment in the formation of teachers in a perspective of an anti-racist education in line with Law nº 10.639/03.